Tokyo ghoul. Vol. 5 - Ishida, Sui (VIZ Media, 2016)
Ghouls live among us, the same as normal people in every way - except their craving for human flesh. Ken Kaneki is an ordinary college student until a violent encounter turns him into the first half-human half-ghoul hybrid. Trapped between two worlds, he must survive Ghoul turf wars, learn more about Ghoul society and master his new powers. Kaneki meets Shu Tsukiyama, known as The Gourmet for his interesting and sadistic tastes. And Kaneki learns more about what happened to Rize and what it means to be a One-Eyed Ghoul.